Bentonite-based sodium alginate/ dextrin cross-linked poly (acrylic acid) hydrogel nanohybrids for facile removal of paraquat herbicide from aqueous solutions - GÜNDÜZ, OĞUZHAN (My University, 2022)
© 2021 Elsevier LtdRemoval of hazardous herbicides from the aqueous solution is critical for overcoming health-related issues across the wider population. In the current work, we have prepared sodium alginate (SAlg), dextrin, and acrylic acid (AA) based cross-linked hydrogels, composed of bentonite incorporated in the biocompatible hydrogel matrix. This hydrogel composite can remove highly toxic herbicide paraquat (PQ). As-synthesised hydrogel (SAlg/dextrin-cl-PAA) and hydrogel composite (SAlg/dextrin-cl-PAA/bentonite) were further analysed by infra-red spectroscopy (FTIR), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and thermogravimetric analysis (TGA/DSC). For the first time, PQ adsorption onto sodium and dextrin-based hydrogel was also evaluated. The measured highest removal capacities were 76.923 and 90.909 mg g−1 for the SAlg/dextrin-cl-PAA and SAlg/dextrin-cl-PAA/bentonite, respectively. Pseudo-second-order (PSO) and Langmuir isotherm models have shown to be best suited for accurately describing the adsorption mechanism. A thermodynamics study verified that the adsorption of PQ on adsorbents is spontaneous, favourable and exothermic. Moreover, reusability analysis shows that the adsorbents possess good reproducibility even after six successive cycles. The adsorption results demonstrate that the synthesised adsorbents are very efficient for removing herbicides (PQ) from wastewater.
Keywords: Sağlık Bilimleri; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Health Sciences; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Social Sciences and Humanities; Sociology; Life Sciences; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Mühendislik; Farmakoloji ve Toksikoloji; Sosyal Bilimler Genel; MÜHENDİSLİK, ÇEVRE; TOKSİKOLOJİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); Social Sciences (SOC); ENGINEERING; CHEMISTRY; PHARMACOLOGY & TOXICOLOGY; SOCIAL SCIENCES, GENERAL; ENGINEERING, ENVIRONMENTAL; TOXICOLOGY; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Environmental Engineering; Physical Sciences; General Chemistry; Environmental Chemistry; Pollution; Public Health, Environmental and Occupational Health; Health, Toxicology and Mutagenesis; Sodium alginate; Dextrin; Bentonite; Hydrogel composite; Paraquat removal; METHYLENE-BLUE; EFFICIENT REMOVAL; NANOCOMPOSITE SYNTHESIS; ADSORPTION; WATER; ADSORBENT; DYE; CELLULOSE; DEXTRIN; ANTIOXIDANT